2016
DOI: 10.1109/tdmr.2016.2557585
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport Mechanisms in Heavy-Ion Driven Leakage Current in Silicon Carbide Schottky Power Diodes

Abstract: Abstract-Under heavy-ion exposure at sufficiently high reverse bias voltages silicon carbide (SiC) Schottky diodes are observed to exhibit gradual increases in leakage current with increasing ion fluence. Heavy-ion exposure alters the overall reverse current-voltage characteristics of these diodes, leaving the forward characteristics practically unchanged. This paper discusses the charge transport mechanisms in the heavy-ion damaged SiC Schottky diodes. A macro model, describing the reverse current-voltage cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…3 for a very low ion flux. Significant discrete increases in leakage current are evident for individual ion strikes, consistent with earlier experiments [9,10]. Leakage current increases as long as the beam is on.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…3 for a very low ion flux. Significant discrete increases in leakage current are evident for individual ion strikes, consistent with earlier experiments [9,10]. Leakage current increases as long as the beam is on.…”
Section: Introductionsupporting
confidence: 87%
“…In addition, efficient Schottky switching diodes in SiC can be manufactured that exhibit very low on-state voltage and minimal turn-off switching loss with almost no reverserecovery behavior, which makes SiC a good candidate for space power conversion applications. However, the sensitivity of SiC power devices (MOSFETs and diodes) to particle radiation has been found to be higher than expected, given the wide bandgap and high critical electric field, as shown by multiple researchers who have consistently measured significant leakage current increases and single-event burnout in SiC devices [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Heavy-ion exposure has been shown to increase reverse leakage current in SiC Schottky diodes, when a sufficient reverse bias is applied during radiation exposure [6], [7], [15]. When an ion beam hits the device at an angle off normal incidence, a similar, but weaker, effect is observed [11].…”
Section: Resultsmentioning
confidence: 99%
“…The silicon power devices typically exhibit separate regions of destructive and nondestructive response as a function of voltage [4], [5]. In addition to these two regions, SiC Schottky devices have been reported to exhibit also a third region where devices suffer from gradual degradation under heavy-ion exposure [2], [6], [7]. This gradual degradation complicates the assessment of SiC parts for catastrophic failures like Single Event Burnout (SEB).…”
Section: Introductionmentioning
confidence: 99%
“…In the past ten years, scientists in Finland and other countries have studied the influence of high-energy particles on SiC devices. It is reported that Schottky devices, made of SiC [118], Si [119], and GaN [120], gradually decompose under heavy-ion exposure. As the bias level is high enough, SiC Schottky devices also go through catastrophic SEB (single-event burnout) during irradiation.…”
Section: Influence Of High-energy Particles On Semiconductor Devicesmentioning
confidence: 99%